Effect of surface roughness on runoff, infiltration and soil loss - Bahddou, Sophia; Otten, Wilfred; Rickson, R. Jane; Whalley, W. Richard; Shin, Ho-Chul; El Gharous, Mohamed (Cranfield University, 2023)
The excel spreadsheet presents the raw data generated from the experiments quantifying soil erosion that are described in the paper by Bahddou et al., 2023, published in Geoderma (Bahddou et al., 2023. Changes in soil surface properties under simulated rainfall and the effect of surface roughness on runoff, infiltration and soil loss). The experimental design and the statistical method are mentioned in the methodology section of the paper. The soil surface roughness data is expressed in two columns (E-F) presenting the measurements before and after the rainfall event (Table 3 and Figure 4 of the paper by Bahddou et al). The variables of the runoff, infiltrate, soil loss and sediment concentration are expressed in the columns G-R, where each variable is expressed in three columns presenting the 1st fifteen minutes of the rainfall event, the 2nd fifteen minutes of the rainfall event and the total 30 minutes of the rainfall event (Table 4 and Figures 6 and 7 in the paper by Bahddou et al., 2023). The columns S-U present the splash erosion after 30 minutes of rainfall, including the measurements on the ridges and in the furrows of Treatment B. More details are in the Materials and Methods section and the Results sections of the publication.
Keywords: Soil erosion; Soil surface roughness